Toward a safer school environment: A mixed-methods analysis of bullying and its impact on romanian middle school students - Claudiu Coman; Anna Bucs; Angelica Banca; Marcel Iordache; Gabriela Motoi (PLoS ONE, 2026)
Our study investigated the complex and nuanced phenomenon of bullying in the Romanian educational context, using a mixed methods approach. Its objective was to analyze the implications and effects of bullying on students, the school environment, and school safety and to propose recommendations to elevate and enhance existing bullying prevention programs. The qualitative data was collected using the adopted Owelus Questionnaire and analyzed to determine the prevalence of bullying and its effects. Qualitative data was collected by conducting semi-structured interviews with different stakeholders such as teachers, parents, and experts who expressed their insights on the intricacies of this harmful and prevalent phenomenon in the Romanian educational context, their experiences, and possible risk factors. The results highlight a significant and negative effect on the emotional well-being of students. In addition, our research identified the different perceptions of the interviewed stakeholders: teachers, parents, and experts, highlighting the need for targeted and multiple interventions that include all key participants in the bullying phenomenon. This study suggests a better collaboration among teachers, parents, and the school community. Conclusions include recommendations for creating intervention programs that are comprehensive, specific, and efficient given the resources available to the Romanian educational system.